Species And Abundance Of Fish In The Seagrass Beds Napomanuk Island, West Likupang, North Minahasa - Ardi Lensun; Nego E. Bataragoa; Ari B. Rondonuwu (Sam Ratulangi University, 2021)
This study aims to know fish genera, species abundance, and biomass in the seagrass bed of Napomanuk island. It applied swept area method using a beach seine 60 m long 3 m depth with 0.5 cm mesh at the purse and 1 cm at the wings. The study was conducted at full moon and new moon period at both high tide and low tide. There were 55 fish species of 31 families recorded. In full moon period, 37 species occurred at high tide. The species abundance (Ki) ranged from 0.0004/m2 to 0.0126/m2 with the highest in Diodon liturosus, 0.0126/m2. The biomass abundance (Kb) ranged from 0.0019 g/m2 to 1.133 g/m2, with the highest in Diodon liturosus,1.133 g/m2. At low tide, there were 16 species recorded with the species abundance (Ki) of 0.0006/m2 to 0.0037/m2 and the highest in Diodon liturosus 0.0037/m2 and the biomass abundance (Kb) of 0.0002 g/m2 to 0.2949 g/m2 and the highest in Diodon liturosus 0.2949 g/m2. In new moon period, there were 29 species recorded at high tide. The species abundance (Ki) ranged from 0.0004/m2 to 0.0041/m2 with the highest in Diodon liturosus with the highest in Diodon liturosus, 0.0041/m2. The biomass abundance (Kb) ranged from 0.0007 g/m2 to 0.4015 g/m2, with the highest in Diodon liturosus 0.4015 g/m2. At low tide, there were 22 species recorded. The species abundance (Ki) ranged from 0.0004/m2 to 0.0096/m2 with the highest in Diodon liturosus, 0.0096/m2. The biomass abundance (Kb) ranged from 0.0011 g/m2 to 1.1119 g/m2, with the highest in Diodon liturosus, 1.1119 g/m2.Keyword: Seagrass Ecosystem, Abundance, Species, Biomass, Napomanuk Island ABSTRAKPenelitian ini bertujuan untuk mengetahui jenis ikan dan kelimpahan individu dan biomassa ikan di Padang Lamun Pulau Napomanuk. Metode penelitian menggunakan metode daerah sapuan (sweept area) dengan menggunakan pukat pantai dengan panjang 60 m, tinggi bagian kantong 3 m, mata jaring kantong 0,5 cm, dan mata jaring sayap 1 cm. Penelitian dilaksanakan pada fase bulan purnama dan bulan baru baik waktu air pasang maupun air surut. Selama penelitian ini ditemukan 31 famili dan 55 spesies ikan. Pada periode air pasang bulan purnama terdapat 37 spesies ikan. Kelimpahan individu (Ki) berkisar antara 0,0004/m2 sampai 0,0126/m2, dengan nilai Ki terbesar pada spesies Diodon liturosus 0,0126/m2. Kelimpahan biomassa (Kb) berkisarantara 0,0019 g/m2 sampai 1,133 g/m2, dengan nilai Kb terbesar pada spesies Diodon liturosus 1,133 g/m2. Pada periode air surut bulan purnama terdapat 16 spesies ikan. Kelimpahan individu (Ki) berkisar antara 0,0006/m2 sampai 0,0037/m2, dengan nilai Ki terbesar pada spesies Diodon liturosus 0,0037/m2. Kelimpahan biomassa (Kb) berkisar antara 0,0002 g/m2 sampai 0,2949 g/m2, dengan nilai Kb terbesar pada spesies Diodon liturosus 0,2949 g/m2. Pada periode air pasang bulan baru terdapat 29 spesies ikan. Kelimpahan individu (Ki) berkisar antara 0,0004/m2 sampai 0,0041/m2 dengan nilai Ki terbesar pada spesies Diodon liturosus 0,0041/m2. Kelimpahan biomassa (Kb) berkisar antara 0,0007 g/m2 sampai 0,4015 g/m2, dengan nilai Kb terbesar pada spesies Diodon liturosus 0,4015 g/m2. Pada periode air surut bulan baru terdapat 22 spesies ikan. Kelimpahan individu (Ki) berkisar antara 0,0004/m2 sampai 0,0096/m2 dengan nilai Ki terbesar pada spesies Diodon liturosus 0,0096/m2. Kelimpahan biomassa (Kb) berkisar antara 0,0011 g/m2 sampai 1,1119 g/m2, dengan nilai Kb terbesar pada spesies Diodon liturosus 1,1119 g/m2.Kata kunci : Ekosistem Lamun, Kelimpahan, Spesies, Biomassa, Pulau Napomanuk